The Sunday of fiction : the modern French eccentric - Schulman, Peter, 1964- (Purdue studies in Romance literatures, 2003)
"In a world of increasing conformity, the modern eccentric can be seen as a contemporary hero and guardian of individualism. With this rudimentary notion of the eccentric in mind, this book defines the modern eccentric in twentieth-century French literature by tracing the eccentric's relationship to time, space, and society. While previous studies have focused on the notion of eccentricity in purely formal terms, The Sunday of Fiction delineates the eccentric as a fully fictional character